Dynamics and Interactions of OmpF and LPS: Influence on Pore Accessibility and Ion Permeability - Patel, Dhilon S. (Biophys J, 2016)
The asymmetric outer membrane of Gram-negative bacteria is formed of the inner leaflet with phospholipids and the outer leaflet with lipopolysaccharides (LPS). Outer membrane protein F (OmpF) is a trimeric porin responsible for the passive transport of small molecules across the outer membrane of Escherichia coli. Here, we report the impact of different levels of heterogeneity in LPS environments on the structure and dynamics of OmpF using all-atom molecular dynamics simulations. The simulations provide insight into the flexibility and dynamics of LPS components that are highly dependent on local environments, with lipid A being the most rigid and O-antigen being the most flexible. Increased flexibility of O-antigen polysaccharides is observed in heterogeneous LPS systems, where the adjacent O-antigen repeating units are weakly interacting and thus more dynamic, compared to homogeneous LPS systems in which LPS interacts strongly with each other with limited overall flexibility due to dense packing. The model systems were validated by comparing molecular-level details of interactions between OmpF surface residues and LPS core sugars with experimental data, establishing the importance of LPS core oligosaccharides in shielding OmpF surface epitopes recognized by monoclonal antibodies. There are LPS environmental influences on the movement of bulk ions (K(+) and Cl(−)), but the ion selectivity of OmpF is mainly affected by bulk ion concentration.